2017
DOI: 10.3311/ppso.10281
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Absorptive Capabilities to Export Performance

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Specifically, this theory focuses on investment in human capital (Lucas, 1988). The improvement in human capital will help firms to adapt in the competitive market (França and Rua, 2017) and lead to faster innovation. FDI is an important source to gain more knowledge by newer technology and higher capital stock (Anwar and Nguyen, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, this theory focuses on investment in human capital (Lucas, 1988). The improvement in human capital will help firms to adapt in the competitive market (França and Rua, 2017) and lead to faster innovation. FDI is an important source to gain more knowledge by newer technology and higher capital stock (Anwar and Nguyen, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another significant finding with respect to SME demonstrated that the company's absorptive capacity has a positive and significant influence on their export performance. França and Rua (2017) maintain that companies are able to acquire, transform and exploit knowledge through: informal knowledge gathering, clear definition of tasks, analysis and discussion of market trends and new product development, among others.…”
Section: Background 21 Absorptive Capacitymentioning
confidence: 99%
“…Another significant finding with respect to SME demonstrated that the company's absorptive capacity has a positive and significant influence on their export performance. França and Rua (2017) maintain that companies are able to acquire, transform and exploit knowledge through: informal knowledge gathering, clear definition of tasks, analysis and discussion of market trends and new product development, among others. Furthermore, absorptive capacity has been strongly linked to the concept of open innovation since companies that rely on this type of innovation are always screening their environment to search for technology and knowledge and do not exclusively rely on inhouse R&D (Spithoven et al, 2011); therefore, absorptive capacity has been defined as a precondition to open innovation.…”
Section: Absorptive Capacitymentioning
confidence: 99%
See 1 more Smart Citation